HLA Gene Polymorphisms in Romanian Patients with Chronic Lymphocytic Leukemia - Maria Tizu; Bogdan Calenic; Mihai Hârza; Bogdan M. Cristea; Ion Maruntelu; Andreea M. Caragea; Adriana Talangescu; Alina Dima; Alexandra E. Constantinescu; Ileana Constantinescu (Genetics Research)
Background and Objectives. Numerous genome-wide association studies have highlighted that chronic lymphocytic leukemia (CLL) is a lymphoproliferative disorder with an important genetic component. An important number of genes have been implicated in CLL etiology, with some of the most important being human leukocyte antigen (HLA) genes. The aim of this study was to analyze the association of CLL with certain HLA alleles in the Romanian population and to compare our results with previous findings. Materials and Methods. This study included 66 patients with CLL, diagnosed between 2020 and 2022, and 100 healthy controls. HLA class I and class II genes (HLA-A/B/C, HLA-DQA1/DQB1/DPA1/DPB1, and HLA-DRB1/3/4/5) were investigated using next-generation sequencing technology. Results. Several HLA alleles were strongly associated with CLL. The most important finding was that HLA-DRB1∗04:02:01 (p=0.001, OR = 1.05) and HLA-DRB3∗02:01:01 (p=0.009, OR = 1.03) have a predisposing role in CLL development. Moreover, we identified that HLA-A∗24:02:01 0.01 (p=0.01, OR = 0.38), HLA-DQA1∗05:05:01 (p=0.01, OR = 0.56), HLA-DQB1∗03:02:01 (p=0.03, OR = 0.40), and HLA-DRB4∗01:03:01 (p=0.03, OR = 0.54 alleles have protective roles. Correlations between HLA expression and gender showed that women had a higher expression of protective HLA alleles when compared to men. Conclusions. Our data are the first to indicate that in Romanian patients with CLL, the HLA-A∗24:02:01 and HLA-DQA1∗05:05:01 alleles have a protective role against CLL development, whereas HLA-DRB1∗04:02:01 and HLA-DRB3∗02:01:01alleles are positively associated with CLL.